2021
DOI: 10.3389/fphys.2020.542950
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Enzymes of the Urea Cycle Cluster at the Inner Mitochondrial Membrane

Abstract: Mitochondrial enzymes involved in energy transformation are organized into multiprotein complexes that channel the reaction intermediates for efficient ATP production. Three of the mammalian urea cycle enzymes: N-acetylglutamate synthase (NAGS), carbamylphosphate synthetase 1 (CPS1), and ornithine transcarbamylase (OTC) reside in the mitochondria. Urea cycle is required to convert ammonia into urea and protect the brain from ammonia toxicity. Urea cycle intermediates are tightly channeled in and out of mitocho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…Formation of CPS1-OTC complexes would regulate the channeling of CP into the OTC reaction that has been observed experimentally (Cohen et al, 1992). CPS1 can further interact with mitochondrial N-acetylglutamate synthase (NAGS) possibly via the variable segment domain (Haskins et al, 2020). NAGS has a key regulatory function in generating N-acetyl-glutamate, a mandatory positive allosteric effector of CPS (Figure 1).…”
Section: Structural and Functional Interactions In The Urea Cyclementioning
confidence: 89%
See 1 more Smart Citation
“…Formation of CPS1-OTC complexes would regulate the channeling of CP into the OTC reaction that has been observed experimentally (Cohen et al, 1992). CPS1 can further interact with mitochondrial N-acetylglutamate synthase (NAGS) possibly via the variable segment domain (Haskins et al, 2020). NAGS has a key regulatory function in generating N-acetyl-glutamate, a mandatory positive allosteric effector of CPS (Figure 1).…”
Section: Structural and Functional Interactions In The Urea Cyclementioning
confidence: 89%
“…NAGS has a key regulatory function in generating N-acetyl-glutamate, a mandatory positive allosteric effector of CPS (Figure 1). A more recent study confirmed that the three mitochondrial urea cycle enzymes NAGS, CPS1, and OTC can interact and form clusters at the inner mitochondrial membrane (Haskins et al, 2020) which would facilitate metabolite flux through the mitochondrial part of the urea cycle.…”
Section: Structural and Functional Interactions In The Urea Cyclementioning
confidence: 92%
“…For instance, it is known that glycine is modulated by serine hydroxymethyl transferase [20]. Carbamoyl-phosphate synthetase 1, ornithine transcarbamylase and n-acetylglutamate synthase are essential enzymes in regulating the urea cycle [21]. Thus, the protein and gene expression levels of these proteins are involved in the modulation of the levels of these metabolic parameters in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…4 ) were also related to amino acid. For example, ammonia recycling is responsible for recycling of ammonia into central amino acid metabolism [ 57 ], Urea Cycle converts excess ammonia into urea in the mitochondria of liver cells [ 58 ], Glucose-alanine Cycle refers to the series of reactions in which amino groups and carbons from muscle are transported to the liver [ 59 ]. From the results of MESA (Fig.…”
Section: Discussionmentioning
confidence: 99%